84.3k views
3 votes
Factor the expression below.

49a2 – 25b2

Which of the following binomials is a factor of the expression?

User Anton Kim
by
6.5k points

2 Answers

2 votes
(7a+5b)(7a-5b) is correct
User Sundar G
by
5.4k points
0 votes

Answer:


49a^(2) - 25b^(2) = (7a + 5b)(7a - 5b)

Explanation:

The most common factorization of binomial expressions are:


(x + y)^(2) = x^(2) + 2xy + y^(2)


(x - y)^(2) = x^(2) - 2xy + y^(2)


(x + y)*(x - y) = x^(2) - y^(2)

This goes both ways, that is,
(x + y)*(x - y) = x^(2) - y^(2), just as,
x^(2) - y^(2) = [tex](x + y)*(x - y)

So


49a^(2) - 25b^(2) = (7a + 5b)(7a - 5b)

User Ycon
by
6.7k points